Pengaruh Board Diversity Dan Sales Growth Terhadap Financial Distress Yang Dimoderasi Oleh Board Remuneration Pada Perusahaan Pertambangan Di Indonesia - Bangun, Bastanna Erlayas; Bahtiar Usman; Hartini (LPPM UBP, 2024)
This study aims to analyze influence of the independent variables Board Diversity (consisting of Demographic Diversity and Cognitive Diversity) and Sales Growth on the dependent variable Financial Distress with the moderating variable being Board Remuneration and the control variables Firm Size, Company Age, Total Asset Turn Over in mining companies listed on the BEI (Exchange Indonesian Effect) during the period 2018 - 2022. The study sample was selected using a purposive sampling method so that 43 (forty three) companies were obtained that met the criteria to become the sample. Data analysis used to test the hypothesis is multiple regression analysis using the Eviews-12 program. In predicting the value of financial distress, the author uses the Zmijewski model analysis or what is often known as the X-Score method. Based on the results of study that has been carried out, it is known that the Board Diversity variable, especially the Demographic Diversity variable, has a negative influence on Financial Distress, and the Sales Growth variable for both the Demographic Diversity and Cognitive Diversity variables has a positive influence on Financial Distress. The results of this study also show that the two Board Diversity variables, namely Demographic Diversity and Cognitive Diversity and Sales Growth on Financial Distress are moderated by Board Remuneration, so the one that has an influence is Sales Growth, both for the two components, namely Demographic Diversity and Cognitive Diversity, which have a negative influence.